PENGARUH APLIKASI SISTEM AKUAKULTUR TERTUTUP HIBRID ZERO WATER DISCHARGE-RECIRCULATING AQUACULTURE SYSTEM (ZWD-RAS) DENGAN SUPLEMENTASI PAKAN SINBIOTIK TERHADAP PROFIL KOMUNITAS MIKROBA DAN PERFORMA PERTUMBUHAN SERTA KELULUSHIDUPAN PADA PEMBESARAN UDANG PUTIH (LITOPENAEUS VANNAMEI) - Azizy, Atian
White Shrimp (Litopenaeus vannamei) contributes about 75% of the total shrimp production in Indonesia. The Indonesian Ministry of Maritime Affairs and Fisheries is now targeting a 250% increase in shrimp exports by 2024. However, low water quality and the issue of infectious diseases by pathogenic bacteria such as vibriosis are still major problems in white shrimp culture. Several alternative strategies that can be done to deal with these problems are: (1) the application of a closed aquaculture system such as the ZWD-RAS hybrid which can maintain the stability of the physical, chemical, and biological parameters of culture water quality and improve aquaculture performance; (2) cultivation at low salinity to facilitate disease control; and (3) feeding with synbiotic supplementation which is a mixture of probiotics and prebiotics to improve health and disease resistance in white shrimp. In this study, the profile of the microbial community formed using the culturedependent method was compared between ZWD-RAS hybrid treatment with synbiotic feed ('HS'), ZWD-RAS hybrid with commercial feed ('HK'), semi-batch control with synbiotic feed. ('KS'), and semi-batch control with commercial feed ('KK') also the relationship between growth and survival of white shrimp during 45 days of the nursery period. The research began with the preparation and conditioning of the ZWD-RAS hybrid system by adding the probiotic Halomonas alkaliphila and the microalgae Chaetoceros calcitrans to the ZWD tank; and the manufacture of synbiotic feed by mixing commercial feed with H. alkaliphila, red seaweed Kappaphycus alvarezii, and microalgae Spirulina sp. During cultivation, water quality parameters were measured as well as the addition of microbes to the ZWD tank regularly. Diversity, dominance, and similarity index were calculated on the water microbial community on days 0, 14, 28, and 45 and the shrimp gut microbial community on day 45. Observation of the total plate count (TPC) on NA medium showed that the total heterotrophic bacteria in the hybrid system water samples (HS and HK) was higher than the control (KS and KK); while TPC on TCBS medium indicated the number of Vibrio sp. lower in the hybrid treatment compared to the control. Relatively similar results were observed in samples of shrimp intestines with an indication of the number of Vibrio sp. which was lower in the HS and KS treatments compared to the HK and KK treatments. The index values of diversity, dominance, and similarity were found to fluctuate every time in all treatments. The total white shrimp biomass from HS, HK, KS, and KK was found to be 141.40±35.21 gr, respectively; 63.75±21.83 gr; 108.50±13.03 g; and 66.15±8.12gr. The survival rates of white shrimp from HS, HK, KS, and KK were 83.0±0.2%, respectively; 83.0±0.1%; 71.0±0.0%; and 53.0±0.1%. From the overall results of this study, it was concluded that synbiotic feed supplementation and the application of the ZWD-RAS hybrid system were able to maintain the stability of culture water quality, including microbiological parameters, as well as improve the growth and survival performance of white shrimp at the nursery stage.